2014
DOI: 10.1177/0009922814553430
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Harassment in Middle and High School Children and Effects on Physical and Mental Health

Abstract: Sexual harassment can be physical interaction and touching, as well as, psychological, environmental, or via Internet and text messaging. An online survey in an urban clinic asked children, aged 12 to 18 years the following: demographic data, height and weight, chronic medical conditions, healthcare use, questions concerning sexual harassment-witnessed and exposure, and finally questions from the Pediatric Symptom Checklist (PSC-35). Overall, 124 of 210 (59%) of the 12- to 18-year-olds surveyed had experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 25 publications
3
44
1
Order By: Relevance
“…Cortina and colleagues [13] found a rate of 50% among female university students in the United States. In another sample of 118 adolescents 12–18 years old, 69% had experienced sexual harassment [28]. In the control group of a Swedish study of female elite athletes 15–39 years old, 59% reported sexual harassment [29].…”
Section: Discussionmentioning
confidence: 99%
“…Cortina and colleagues [13] found a rate of 50% among female university students in the United States. In another sample of 118 adolescents 12–18 years old, 69% had experienced sexual harassment [28]. In the control group of a Swedish study of female elite athletes 15–39 years old, 59% reported sexual harassment [29].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that 90% of adolescent girls have been the target of sexual harassment at least once, and between one in four and one in five women in college have been the victim of sexual assault (Leaper & Brown, 2008;Muehlenhard et al, 2017). Research has documented that being the target of sexual harassment and assault has longterm consequences on physical, mental, and emotional health, such as disordered eating, depression, anxiety, fear, anger, humiliation, distrust, and post-traumatic stress syndrome (e.g., Chiodo et al, 2009;Eom et al, 2015;Goldstein et al, 2007;Jina & Thomas, 2013). Despite the severity and longevity of consequences for the victims of sexual harassment and assault, there are rarely consequences for the perpetrators.…”
mentioning
confidence: 99%
“…Sexual harassment is frequent among young people (Bucchianeri, Eisenberg, Wall, Piran, & Neumark-Sztainer, 2014; Eom, Restaino, Perkins, Neveln, & Harrington, 2015). Some studies show increased prevalence among female respondents (Clear et al, 2014; Eom et al, 2015; Petersen & Hyde, 2013) and others show different prevalence among males and females, according to the type of harassment considered (Bucchianeri et al, 2014; Chiodo, Wolfe, Crooks, Hughes, & Jaffe, 2009).…”
mentioning
confidence: 99%